The effect of financial inclusion on Banks' credit risk: perspective from MENA region - Mohamed Farid, Rami (AUC Knowledge Fountain, 2020)
Financial inclusion is aimed at introducing the undeserved segment of the community to the official financial institutions. It is without doubt that financial inclusion is one of the sustainable development goals to raise the poor's living standards by availing banking services that are not limited to loan acquisition. In this respect, this study aims at testing the relationship between the most used financial inclusion indicators and the ratio of the provision for loan losses to net loan as a proxy for credit risk. Using the Least Square Dummy Variables (LSDV) as estimation equation for non-linear model, it is found that borrowing from financial institutions or through credit card in labour force affects credit risk negatively. Meanwhile debit card ownership affects credit risk positively. Applying these results on the MENA region as the thesis's geographic scope, the countries the most affected by credit risk as a result of financial inclusion programs are Algeria, Egypt, Iraq, Jordan, Kuwait, Libya, Morocco, Syria, Tunisia, UAE, and Yemen. Moreover, post the addition of the longevity effect to the regression equation, these countries need to accumulate enough reserve for loan losses for at least three years. In the light of having two opposing teams in the literature, the thesis is more inclined towards the team supporting financial inclusion as having a positive effect on banks' stability but on the long term.